CDHI promoter hypermethylation and E-cadherin protein expression in infiltrating breast cancer - Caldeira, Jose Roberto F. (2006)
Background: the E-cadherin gene (CDH1) maps, at chromosome 16q22.1, a region often associated with loss of heterozygosity (LOH) in human breast cancer. LOH at this site is thought to lead to loss of function of this tumor suppressor gene and was correlated with decreased disease-free survival, poor prognosis, and metastasis. Differential CpG island methylation in the promoter region of the CDH1 gene might be an alternative way for the loss of expression and function of E-cadherin, leading to loss of tissue integrity, an essential step in tumor progression.Methods: the aim of our study was to assess, by Methylation-Specific Polymerase Chain Reaction (MSP), the methylation pattern of the CDH1 gene and its possible correlation with the expression of E-cadherin and other standard immunohistochemical parameters (Her-2, ER, PgR, p53, and K-67) in a series of 79 primary breast cancers ( 71 infiltrating ductal, 5 infiltrating lobular, 1 metaplastic, 1 apocrine, and 1 papillary carcinoma).Results: CDH1 hypermethylation was observed in 72% of the cases including 52/71 ductal, 4/5 lobular carcinomas and 1 apocrine carcinoma. Reduced levels of E-cadherin protein were observed in 85% of our samples. Although not statistically significant, the levels of E-cadherin expression tended to diminish with the CDH1 promoter region methylation. In the group of 71 ductal cancinomas, most of the cases of showing CDH1 hypermethylation also presented reduced levels of expression of ER and PgR proteins, and a possible association was observed between CDH1 methylation and ER expression ( p = 0.0301, Fisher's exact test). However, this finding was not considered significant after Bonferroni correction of p-value.Conclusion: Our preliminary findings suggested that abnormal CDH1 methylation occurs in high frequencies in infiltrating breast cancers associated with a decrease in E-cadherin expression in a subgroup of cases characterized by loss of expression of other important genes to the mammary carcinogenesis process, probably due to the disruption of the mechanism of maintenance of DNA methylation in tumoral cells.